2013
DOI: 10.3402/tellusb.v65i0.21040
|View full text |Cite
|
Sign up to set email alerts
|

Stable bromine isotopic composition of atmospheric CH<sub>3</sub>Br

Abstract: Tropospheric methyl bromide (CH3Br) is the largest source of bromine to the stratosphere and plays an important role in ozone depletion. Here, the first stable bromine isotope composition (%26dgr%3B81Br) of atmospheric CH3Br is presented. The %26dgr%3B81Br of higher concentration Stockholm samples and free air subarctic Abisko samples suggest a source/background value of %26minus%3B0.04%26plusmn%3B0.28%26permil%3B ranging up to +1.75%26plusmn%3B0.12%26permil%3B. The Stockholm %26dgr%3B81Br versus concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…10), implying that agriculture activities could also have little influence on Br isotope signatures in brackish water. However, it is worth noting that sample 1222 and 1223 show a decrease of the d 81 Br values, probably toward the anthropogenic CH 3 Br mean value of +0.12 ± 0.9‰ (Horst et al, 2013).…”
Section: Genesis Of Brackish Water: Other Processesmentioning
confidence: 96%
See 1 more Smart Citation
“…10), implying that agriculture activities could also have little influence on Br isotope signatures in brackish water. However, it is worth noting that sample 1222 and 1223 show a decrease of the d 81 Br values, probably toward the anthropogenic CH 3 Br mean value of +0.12 ± 0.9‰ (Horst et al, 2013).…”
Section: Genesis Of Brackish Water: Other Processesmentioning
confidence: 96%
“…However, based on the same principle, the authors believe that the same atmospheric process would also result in Br isotope fractionation, and make the recharge water more enriched in 81 Br. Previous results (Eggenkamp, 2014;Gwynne et al, 2013;Horst et al, 2013) indicated that bromine is enriched from selective atmospheric processes (e.g. photolysis of bromomethane) causing fractionation in marine aerosols during transport, and exhibited the enrichment of 81 Br in groundwater in the recharge area.…”
Section: Genesis Of Brackish Water: Marine Aerosols Inputmentioning
confidence: 96%
“…CH 3 Br may originate from natural and anthropogenic sources. Horst et al (2013) determined the Br isotope composition of methyl bromide at two locations in Sweden. Subarctic samples in northern Sweden were more negative than samples in the Stockholm area.…”
Section: Brominementioning
confidence: 99%
“…Apart from carbon isotope analysis, hydrogen isotope 10 measurements have been demonstrated for CH3Cl (Nadalig et al, 2013;Keppler et al, 2018;Jaeger et al, 2018). For CH3Br bromine isotope analysis was presented in two studies (Horst et al, 2013;Horst et al, 2014).…”
Section: Introductionmentioning
confidence: 99%